Dual Gold‐Catalyzed Cycloaromatization of Unconjugated (E)‐Enediynes. (16th January 2019) - Zamani, Farzad; Babaahmadi, Rasool; Yates, Brian F.; Gardiner, Michael G.; Ariafard, Alireza; Pyne, Stephen G.; Hyland, Christopher J. T.
Abstract: A synthesis of unconjugated ( E )‐enediynes from allenyl amino alcohols is reported and their gold‐catalyzed cascade cycloaromatization to a broad range of enantioenriched substituted isoindolinones has been developed. Experimental and computational studies support the reaction proceeding via a dual‐gold σ, π‐activation mode, involving a key gold‐vinylidene‐ and allenyl‐gold‐containing intermediate.